Clinical performance of metagenomic next-generation sequencing for diagnosis of invasive fungal disease after hematopoietic cell transplant - Zhang, Xiaoying; Zhang, Lingfeng; Li, Yun; Wang, Na; Zhang, Yicheng (Frontiers in Cellular and Infection Microbiology, 2024)
Background Timely diagnosis and appropriate antifungal therapy are critical for improving the prognosis of patients with invasive fungal disease (IFD) after hematopoietic stem cell transplantation (HSCT). We evaluated the performance of metagenomic next-generation sequencing (mNGS) and conventional microbiological testing (CMT), as well as the diagnosis, therapeutic management, and outcomes of IFD after HSCT. Methods We retrospectively studied 189 patients who underwent HSCT and were considered at risk for IFD. In total, 46 patients with IFD were enrolled in this study. The IFD consensus was followed for classifying IFD incidents. Results Forty-six patients were diagnosed with proven/probable (n = 12), possible (n = 27), and undefined (n = 7) IFD. Aspergillus was the most commonly detected fungal genus. Mucormycosis was found in 15 patients; two had Aspergillus, and one had Candida infections. Compared to CMT, mNGS significantly reduced the time required to identify pathogens (P = 0.0016). mNGS had a much higher sensitivity than CMT (84.78% vs. 36.96%; P < 0.0001). A total of 76.09% of patients received antifungal prophylaxis during fungal infections. All Pneumocystis infections occurred later than 100 days after transplantation. Among patients with Pneumocystis infection, 71.43% occurred following sulfonamide withdrawal, and subsequent treatment with sulfonamide alone or in combination with other drugs was effective. Based on the empirical antifungal treatment, the dosages, modes of administration, frequency of administration, or antifungal of 55.26% of the patients were changed according to the mNGS results. The 4-year overall survival rate of patients diagnosed with IFD after transplantation was 71.55% (95% CI, 55.18%–85.82%). Hypoproteinemia and corticosteroid use are independent risk factors for IFD. Conclusion mNGS, which has a high sensitivity and a short detection time, aids in the diagnosis and prognosis of pathogenic fungi. As a powerful technology, mNGS can influence treatment decisions in patients with IFD following HSCT.